Total laparoscopic hysterectomy for enlarged uteri: factors associated with the rate of conversion to open surgery. (18th August 2019) - Cianci, S.; Gueli Alletti, S.; Rumolo, V.; Rosati, A.; Rossitto, C.; Cosentino, F.; Turco, L. C.; Vizzielli, G.; Fagotti, A.; Gallotta, V.; Ciccarone, F.; Scambia, G.; et al.
Abstract: A hysterectomy for enlarged uteri is considered a challenge for gynaecologic surgeons, due to the limit of exposure to surgical spaces. Our objective is to investigate the different variables that may have an impact on the risk of conversion to open surgery. This is a retrospective cohort study consisting of 133 women who were submitted to surgery for uterine fibroids and who underwent total hysterectomy by laparoscopic approach attempt. The median uterus weight was 622 grams (range 301–3882) and the median maximum diameter of the bigger fibroid was 74 mm (range 33–148). We registered 13 (9.8%) cases of conversion to laparotomy. Minor and major post-operative complications were recorded in 4 (3%) and in 4 (3%) cases, respectively. After multivariable analysis, the surgeon's experience (OR: 0.24; 95% CI: 0.06–0.94, p = .027) and a maximum diameter of the biggest fibroid ≥10 cm (4.7; 1.39–15.87; p = .046), but not the uterus weight were associated with the risk of conversion to open surgery. IMPACT STATEMENT: What is already known on this subject? Laparoscopic procedures for enlarged uteri are well described in literature; however, the only parameters that have been studied for the success of a laparoscopic procedure have been the uterus weight and the surgeon's experience. What do the results of this study add? This study aimed to value all the possible variables related to the successful of laparoscopic procedures; in fact, we investigated not only the uterine weight, but in our multivariate analysis, the position of the fibroids, the trocar's setting, etc. were analysed. What are the implications of these findings for clinical practice and/or further research? This study reported novel data about the feasibility of laparoscopic hysterectomy for enlarged uteri. In opposition to the literature, the uterine weight is not a predictive value for laparotomic conversion. Moreover, we discussed the possible reasons of our novel findings. It opens new perspective to create a predictive value of laparoscopic feasibility for the different types of enlarged uteri.